Sidestream cigarette smoke and cardiac autonomic regulation - Valenti, Vitor Engrácia [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Ferreira, Celso; Fonseca, Fernando L. A.; Oliveira, Fernando R.; Sousa, Fernando H. [UNESP]; Rodrigues, Luciano M.; Monteiro, Carlos B. M.; Adami, Fernando; Wajnsztejn, Rubens; Abreu, Luiz Carlos de [UNESP] (Springer Nature, 2013)
Background: The literature has already demonstrated that cigarette influences the cardiovascular system. In this study, we performed a literature review in order to investigate the relationship between sidestream cigarette smoke (SSCS) and cardiac autonomic regulation. Methods. Searches were performed on Medline, SciELO, Lilacs and Cochrane databases using the crossing between the key-words: cigarette smoking, autonomic nervous system, air pollution and heart rate variability. Results: The selected studies indicated that SSCS exposure affects the sympathetic and parasympathetic responses to changes in arterial blood pressure. Moreover, heart rate responses to environmental tobacco smoke are increased in smokers compared to non-smokers. The mechanism involved on this process suggest increased oxidative stress in brainstem areas that regulate the cardiovascular system. Conclusion: Further studies are necessary to add new elements in the literature to improve new therapies to treat cardiovascular disorders in subjects exposed to sidestream cigarette smoke. © 2013 Valenti et al; licensee BioMed Central Ltd.
Keywords: Air pollution; Autonomic nervous system; Cardiovascular physiology; Cigarette smoking; catalase; cigarette smoke; nicotine; air pollution; arterial pressure; autonomic nervous system; brain stem; heart rate; heart rate variability; human; nonhuman; oxidative stress; review